Enhanced Circularly Polarized Luminescence from Reorganized Chiral Emitters on the Skeleton of a Zeolitic Imidazolate Framework. Issue 15 (8th March 2019) - Zhao, Tonghan; Han, Jianlei; Jin, Xue; Liu, Yan; Liu, Minghua; Duan, Pengfei
Abstract: A chiral zeolitic imidazolate framework (ZIF) showing circularly polarized luminescence (CPL) has been successfully constructed by blending binapthyl‐derived chiral emitters with ZIF‐8 rhombic dodecahedron nanoparticles. This approach solves a major trade‐off in CPL‐active materials: the large luminescence dissymmetry factor (g lum ) always suffers from suppression of luminescence efficiency. Compared to the optical properties of chiral emitters, the obtained chiral ZIF nanomaterials showed an enhanced fluorescence efficiency while the | g lum | value is significantly amplified by one order of magnitude. Additionally, enantioselective fluorescence sensing in response to α‐hydroxycarboxylic acids has been enhanced in chiral ZIFs. Reorganization and conjunction of chiral emitters to the skeleton of ZIF nanoparticles can greatly improve both the luminescence quantum yield and circularly polarization, which facilitates the design of more efficient chiroptical materials. Abstract : Knowing their left from right : A chiral zeolitic imidazolate framework showing circularly polarized luminescence has been successfully constructed. It can be used as an enantioselective fluorescence sensor for α‐hydroxycarboxylic acids.